THE EFFECT OF COMMUNICATIVE LANGUAGE TEACHING ON STUDENTS’ SPEAKING SKILLS: A SYSTEMATIC LITERATURE REVIEW - Nurul Kamaliah; Rahmati (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
Speaking skill is a fundamental component of English language proficiency, particularly in English as a Foreign Language (EFL) contexts where opportunities for authentic communication are limited. Communicative Language Teaching (CLT) has been widely promoted as an instructional approach that emphasizes meaningful communication, active interaction, and real-life language use. Although CLT has been extensively implemented in speaking instruction, empirical findings regarding its effectiveness remain fragmented and vary across research designs, assessment methods, and learning contexts. Therefore, this study aims to systematically review and synthesize existing research on the effect of Communicative Language Teaching on students’ speaking skills. This study employed a Systematic Literature Review (SLR) following PRISMA guidelines. The reviewed articles were selected from reputable national and international journals published between 2012 and 2025 using predefined inclusion and exclusion criteria. The findings reveal that CLT generally has a positive and significant impact on students’ speaking skills, including fluency, vocabulary development, pronunciation, grammatical accuracy, and interactive competence. However, the review also identifies several methodological limitations, such as small sample sizes, short intervention durations, and the frequent reliance on perception-based instruments rather than performance-based speaking assessments. These findings highlight the need for more rigorous experimental and longitudinal studies to strengthen the empirical evidence of CLT effectiveness and to support evidence-based practices in EFL speaking instruction